Managing Forests for Both Downstream and Downwind Water - Creed, Irena F.; Jones, Julia A.; Archer, Emma; Claassen, Marius; Ellison, David; McNulty, Steven G.; van Noordwijk, Meine; Vira, Bhaskar; Wei, Xiaohua; Bishop, Kevin; Blanco, Juan A.; Gush, Mark; et al. (Frontiers in Forests and Global Change, 2019)
Forests and trees are key to solving water availability problems in the face of climate change and to achieving the United Nations Sustainable Development Goals. A recent global assessment of forest and water science posed the question: How do forests matter for water? Here we synthesize science from that assessment, which shows that forests and water are an integrated system. We assert that forests, from the tops of their canopies to the base of the soils in which trees are rooted, must be considered a key component in the complex temporal and spatial dimensions of the hydrologic cycle. While it is clear that forests influence both downstream and downwind water availability, their actual impact depends on where they are located and their processes affected by natural and anthropogenic conditions. A holistic approach is needed to manage the connections between forests, water and people in the face of current governance systems that often ignore these connections. We need policy interventions that will lead to forestation strategies that decrease the dangerous rate of loss in forest cover and that – where appropriate – increase the gain in forest cover. We need collective interventions that will integrate transboundary forest and water management to ensure sustainability of water supplies at local, national and continental scales. The United Nations should continue to show leadership by providing forums in which interventions can be discussed, negotiated and monitored, and national governments must collaborate to sustainably manage forests to ensure secure water supplies and equitable and sustainable outcomes.